“Genghis Khans” of the 17th-18th centuries: between politics and religion - Baatr Uchaevich Kitinov (RUDN Journal of World History, 2023)
The Mongolian peoples traditionally associated crucial events and processes with the name of Genghis Khan. Nonetheless, that name acquired a nominal significance in one sphere, specifically as a title or an auxiliary name to the first, where it became a special name. The Genghis Khan name itself held a holy and tabooed implication that guided its subsequent realization. The study aims to investigate the impact of religion on the utilisation of Genghis Khan’s title by the Mongolian leaders during the XVII- XVIII centuries. The study focuses on two leaders of Mongolian peoples, the Chakhar in the east and the Oirat-Hoshut in the west, to examine the uniformity and diversity of interpreting and implementing this name as a title. They were Ligdan and Lkhavzan, with Ligdan being a direct descendant of Genghis Khan and Lkhavzan was considered to be a descendant of Khabutu, the younger brother of Genghis Khan. The author came to the following conclusions: such use of Genghis Khan’s name became possible due to the influence of a number of factors that actualised Genghis Khan’s name: 1) the struggle against separatism under the influence of external force; 2) the desire to “start anew”, to lead a “new era of prosperity”; 3) the need to identify oneself as a true leader under the increasing role of religion. The scientific contribution is to determine the multidimensional meaning of Genghis Khan’s name; its use as a title had common grounds and characteristics, and in general had the expected (albeit in the short term) results.